Heart Half Implementation Sharia Banking In Indonesia - Dwi Saputro, Anip; Rois, Adib Khusnul; Bazi, Uzair Al (IKONOMIKA, 2018)
Islamic banking in Indonesia has been regulated in the law, namely Law number 10 of 1998 concerning amendments to Law number 7 of 1992 concerning banking. As time goes by, the existing Islamic banking practices are starting to be questioned, questioned, and criticized, because there are those considered deviant even out of the sharia corridor itself. Against various problems that exist in Islamic banking, it needs to be addressed appropriately. By understanding the nature of the principle of tadrij fii tasyri, we are required to better understand and focus on the processes and stages in the implementation of syariah banking. So that with all the problems of Islamic banking faced now, it must be understood that this is still the stages, not the end and purpose of the application of Islamic banking it self. However, the main problem in the implementation of Islamic banking is the commitment. Islamic banking is in a comfortable zone with its current format. Efforts to implement Islamic banking are still half-hearted, even less serious. Even though there is a lot of criticism embedded in Islamic banking, starting from the practice of improper contracting, Human Resources (HR) who are not competent with the sharia itself, and banking products that are less adaptive and responsive. Keywords: Implementation, Commitment, HR, Product and Agreement, Tadrij fii Tasyri